A chlorhexidine conundrum after an epidural delivery: The difficulty of differentiating between chlorhexidine burns and hypersensitivity reactions - Stephanie C Blake; Stephanie O'Dea; Dedee F Murrell (Wolters Kluwer, 2019)
Chlorhexidine is a commonly used disinfectant throughout Australian hospitals. It is responsible for a number of iatrogenic complications. We describe a case of 27-yearold female who sustained a severe, blistering reaction at the site of chlorhexidine application, associated with significant pain. This reaction was initially managed with wet dressings and topical corticosteroids, but there was no improvement in pain or rash. Management was then changed to silver-coated polyethylene mesh dressings, with resolution of pain and rash after four days. No debridement was required, and area healed without scarring.Chlorhexidine is associated with a number of hypersensitivity reactions, ranging from anaphylaxis to irritant and allergic contact dermatitis. However, physical or chemical burns remain an underrecognised complication of chlorhexidine use. Intra-operatively, there is a risk of physical burn secondary to pooled chlorhexidine catching alight after cautery is applied, and this has been described in ten cases in the literature. Chemical burns from exposure to chlorhexidine can occur in neonatal patients, and in adult patients where a tourniquet has been used.It can be difficult to differentiate between chlorhexidine hypersentivity and burns clinically. When evaluating these patients, a differential diagnosis of burns should be considered, particularly if patients are not responsive to first line therapies. Surgeons and anaesthetists should consider the risk of burns when in theatres, and prevent any pooling of chlorhexidine - particularly when cautery is being used. Using chlorhexidine without alcohol, and allowing at least three minutes for the solution to dry can further reduce the risk of surgical fires. Keywords: Chlorhexidine, irritant dermatitis, burns, chemical